Jaminan Perlindungan Profesi Penilai Publik dalam Konstruksi Peraturan Menteri Keuangan Nomor 56/PMK.01/2017 Tentang Perubahan Atas Peraturan Menteri Keuangan Nomor 101/Pmk.01/2014 Tentang Penilai Publik - Abraham Samuel Amanupunjo; Dian Eka Prastiwi (Rechtsregel : Jurnal Ilmu Hukum, 2020)
The existence of appraisers in Indonesia has not yet been regulated in aseparate law. The function of appraisers is to increase the society trust.Appraisal services business is a business that is very vulnerable to the markup game or decrease the value of an asset or property in accordance with thepurpose of the valuation. The collateral appraisal process by the PublicAppraiser must be based on the Indonesian Appraiser Code of Ethics (KEPI)and the Indonesian Appraisal Standard (SPI) and the facts that areobjectively available. Done without any tendency on personal interests orinfluence of the assignor and / or service user. If the appraisal process is notcarried out according to these things, the Public Appraiser can be said to bemalpractice. Therefore, to carry out an assessment needs guidelines or rules,so that it is not making it up. So far, the rules that form the basis of appraisalservice activities are the Appraisal Services Code of Ethics, the current codeof ethics is the Indonesian Appraiser Code of Ethics (KEPI) and theIndonesian Valuation Standard (SPI). The two guidelines and rules areactually not enough to regulate the activities of the Appraisal Service and avariety of strict regulations are needed, so that it does not cause variousproblems as currently. Meanwhile the regulations governing PublicAppraisers are only Ministerial-level Regulations, namely Minister ofFinance Regulation (PMK) No. 56 / PMK.01 / 2017 concerning changes to theMinister of Finance Regulation (PMK) No. 101 / PMK.01 / 2014 concerningPublic Appraisers which is not equipped with strict sanctions but is limited toadministrative sanctions, so it has not provided legal certainty and guaranteeof protection for the Public Appraiser in carrying out his profession.